On e-convex functions and e-subdifferentials in locally convex spaces. (4th May 2023) - Alizadeh, Mohammad Hossein
Abstract : We introduce and study the notion of e -subdifferential for an e -convex function in locally convex spaces. Some relationships between the e -subdifferential and the Clarke–Rockafellar subdifferential are established. Besides, the e -convex functions are characterized. Moreover, some results regarding the locally Lipschitz properties of e -convex functions are obtained.